2012
DOI: 10.1017/s1368980012005253
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability and construct validity of the DOiT (Dutch Obesity Intervention in Teenagers) questionnaire: measuring energy balance-related behaviours in Dutch adolescents

Abstract: Objective: Adequate assessment of energy balance-related behaviours in adolescents is essential to develop and evaluate effective obesity prevention programmes. The present study examined the test-retest reliability and construct validity of a questionnaire assessing energy balance-related behaviours in adolescents during the evaluation of the DOiT (Dutch Obesity Intervention in Teenagers) intervention. Design: To assess test-retest reliability, adolescents filled in the questionnaire twice (n 111). To assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…This might have led to social desirability and recall bias. Although the questionnaire showed acceptable reliability and validity [ 27 ], the questionnaire targeted only traditional screen devices (i.e., time spent on computer use and television viewing). Adolescents reported to the research team that they found the questions assessing computer and screen time difficult to answer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might have led to social desirability and recall bias. Although the questionnaire showed acceptable reliability and validity [ 27 ], the questionnaire targeted only traditional screen devices (i.e., time spent on computer use and television viewing). Adolescents reported to the research team that they found the questions assessing computer and screen time difficult to answer.…”
Section: Discussionmentioning
confidence: 99%
“…Six behavioural mediators were assessed in the DOiT questionnaire: consumption of SCB, consumption of high-energy snacks/sweets, sport participation, active transport to school, screen time (TV viewing and computer use) and breakfast consumption. Details on the questionnaire can be found elsewhere [ 27 ]. The questionnaire showed good test-retest reliability and moderate to good construct validity for the majority of items.…”
Section: Methodsmentioning
confidence: 99%
“…A questionnaire is developed containing questions on: the number of small (eg, crisps, nuts and chocolate) and large (eg, hamburger, fries and pizza) snacks children eat; the number of sugar-sweetened beverages they drink; their sports and outdoor play participation; their attitude towards sports and outdoor play; their screen behaviour and their self-rated health. The questionnaire is based on validated items from the ENERGY-child questionnaire,37 the DOiT questionnaire38 and the EuroQol 39Table 1 presents the questionnaire items, and the validity and reliability of the original items.…”
Section: Methodsmentioning
confidence: 99%
“…A group of at least 120 adolescent girls50 74 75 will be recruited from one school to assess test-retest reliability of the questionnaire over a fortnight 76. To thank them for their time, the participants will be invited to enter a draw for a $A30 gift voucher at each sitting.…”
Section: Methods and Analysismentioning
confidence: 99%